Measuring the Effectivity of Environmental Law : Legal Indicators for Sustainable Development. - Prieur, Michel. (Générations Futures, Paix et Environnement / Future Generations, Peace and the Environment Series, 2021)
This book presents a new method for measuring the effectiveness of national and international environmental law. It is the result of four years of research and experimentation to develop a way to construct legal indicators. The only existing environmental indicators measure only statistical, scientific or economic data.